Informal Sector and Local Government Revenue : The Contribution of Street Vendors - Tutik Rachmawati (Jurnal Administrasi Publik, 2014)
This paper discusses the contribution of street vendors as the majority group of informal sector to the generation of local government revenue. Based on the desk study of the available literature and research reports on informal sector, this paper analyse how local government should tax informal sector to boost its revenue. In the perspective of legalist school, taxing the informal sector will only increase the informal sector activity, hence formalising the informal sector will not be a recommended policy. Other option to tax the informal sector is by the use of informal sector unions which requried an understanding of citizenship and awareness of their civil rights to establish them. This eventually also beneficial for informal sector as the creation of informal sector unions means the creation of networks and associations which enable them having power vis a vis local government. Keywords : informal sector, street vendors, local government revenue